STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT MENGHADAPI PEMBANGUNAN INFRASTRUKTUR JALAN TOL BAWEN-YOGYAKARTA DAN BANDARA YOGYAKARTA INTERNATIONAL AIRPORT (YIA) - Eny Boedi Orbawati; Retno Rusdjijati; Yun Arifatul Fatimah; Oesman Raliby; Didin Saepudin; Awaluddin Setya Aji; Doddy Ardjono; Andreas Pandiangan; Arizal Arizal; Agus Setyowidodo (Jendela Inovasi Daerah, 2021)
The development of toll road and airport transportation infrastructure is considered to have a strategic role in efforts to improve the local economy. The Magelang Municipality area is a strategic place in the construction of the Bawen-Yogyakarta toll road infrastructure and the construction of the Yogyakarta International Airport (YIA). The construction of a toll road with a toll exit located in the city of Magelang and the presence of an airport whose area is adjacent to Magelang Municipality opens up opportunities for the people of Magelang Municipality to get direct and indirect impacts that can improve welfare. This study aims to analyze the strategy of the Magelang Municipality government in dealing with the infrastructure development of the Bawen-Yogyakarta toll road and Yogyakarta International Airport (YIA) so that it can have an impact on improving the welfare of the people of Magelang Municipality. This study resulted in recommendations, namely: the need for a grand design of exit toll development that accommodates the interests of the community, initiation of the Community-Based Economic Development (CBED) program to empower the community by forming several cluster centers or MSME villages, as well as increasing the role of ABGC (Academic, Business-Governmental). – community).